Isolated Lateral Extra-Articular Tenodesis for Ongoing Instability Following Anterior Cruciate Ligament (ACL) Reconstruction with an Intact Graft is Effective and Has Low Surgical Morbidity - Davies, Peter S.E.; Muirhead, Cameron; Mayne, Alistair I.W.; Ebert, Jay R.; Edwards, Peter K.; Simpson, Ashley; Williams, Andy; D'Alessandro, Peter (The Journal of Knee Surgery, 2024)
The management of persisting instability following anterior cruciate ligament reconstruction (ACLR) includes isolated lateral extra-articular tenodesis (LEAT). The present study investigates the outcomes following isolated LEAT to address ongoing instability following ACLR without LEAT. Patients with ongoing symptomatic instability following ACLR with a radiologically intact and well-positioned graft who underwent an isolated LEAT between January 2017 and March 2022 were retrospectively recruited. Patients completed patient-reported outcome measures at baseline and mean 26 months postoperatively. Twelve knees in 11 patients underwent an isolated LEAT. All Knee Injury and Osteoarthritis Outcome Score domains improved significantly between pre- and postoperative measurements (pain 60.9–91.7, p = 0.002; symptoms 62.5–93.8, p = 0.003; activities of daily living 64.3–95.2, p = 0.002; sport 61.9–82.5, p = 0.012; quality of life 17.2–80.2, p = 0.002). One patient required revision ACL surgery 19 months following their subsequent LEAT procedure. An isolated LEAT demonstrated clinically significant improvements in patient function and activity with acceptable surgical morbidity and should be considered as an option for appropriate cases with instability despite an intact ACL graft.Level of evidence Level IV prospective case series
Keywords: ACL; anterior cruciate ligament; instability; PROMs; patient-reported outcome measure; instability; lateral tenodesis; LET; LEAT